Misfortune Verbal Humor Representing Sudanese as Community Identity - Nurfithri (Ma'soem University, 2026)
Humor serves as a communicative strategy that reflects cultural values and shapes interpersonal relationships. This study investigates verbal humor in Sundanese conversations through the lens of the Script-based Semantic Theory of Humor (SSTH). Using recorded and transcribed dialogues between Sundanese speakers, the analysis explores the presence of script oppositions and logical mechanisms that generate humorous effects. The findings reveal that humor in Sundanese discourse frequently emerges from incongruities between misfortune and reinterpretation, seriousness and absurdity, or reality and imagination. These humorous constructions function as tools for emotional relief, tension reduction, and the reinforcement of social solidarity. Furthermore, verbal humor reflects the cultural identity of the Sundanese people, emphasizing politeness, warmth, empathy, and indirectness. Rather than ridiculing others, Sundanese humor promotes harmony and collective well-being through laughter. This study contributes to a deeper understanding of how linguistic creativity and cultural norms intersect in the construction of humor within local sociolinguistic contexts.